KETIKA INDONESIA INGIN MENJADI PUSAT KEUANGAN SYARIAH DUNIA - Dian Handayani (Universitas Pamulang, 2018)
AbstractIslamic financial market in Indonesia is initiated by market-driven movements. Sukuk issuance is among of them. Growing market, not only domestic but also international, is one of the motivation in Sovereign Sukuk Law initiative. The success of Sukuk issuance has brought new ambitions to make Indonesia as Islamic financial hub in the world. This study aims to analyze the opportunities, challenges, advantages and disadvantages of Indonesia to become the world's Islamic financial center. The study is conducted based on what Malaysia has done – who claim to become a global hub of Islamic capital markets, and Britain – which is a global financial center and set an ambitious agenda to become a global Islamic financial hub. This study uses descriptive analysis and SWOT analysis. As a result, Indonesia has a lot of potential but a more comprehensive strategy is needed to address the challenges in international financial markets. Keywords: Islamic finance, Sukuk, Sovereign Sukuk, Islamic Financial Hub